Ultrathin Terahertz Planar Elements. Issue 2 (22nd February 2013) - Hu, Dan; Wang, Xinke; Feng, Shengfei; Ye, Jiasheng; Sun, Wenfeng; Kan, Qiang; Klar, Peter J.; Zhang, Yan
<x xml:space="preserve">Abstract</x> Various ultrathin planar optical elements, including cylindrical lens, spherical lens, and phase holograms, are designed based on the interface phase modulation of antenna resonances in the terahertz (THz) range. The focusing and imaging performance of the lenses and image‐reconstruction ability of the pure phase holograms are demonstrated experimentally. In contrast to conventional bulky optical elements where curve surfaces are used to control the light propagation, the manipulations of light propagation for these thin planar optical elements are achieved through designed arrays of complementary V‐shaped antennas in the planar gold films with a thickness of 100 nm (1/4000th of the wavelength of the illuminating light). The adoption of the complementary V‐shaped antennas makes the optical elements have double functions: light propagation manipulation and filtering, which improves the performance of the optical elements by blocking the disturbance from the direct transmission. This research is a significant step towards the reduction of the THz elements size and, therefore, to the development of micro‐integrated THz systems and to other applications where the compaction is necessary. The approach used here can be expanded to multifarious optical elements in different wave bands.